2001
DOI: 10.1046/j.1365-2249.2001.01469.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine expression and synovial pathology in the initiation and spontaneous resolution phases of adjuvant arthritis: Interleukin-17 expression is upregulated in early disease

Abstract: SUMMARYThe aim of this study was to understand the immune processes controlling the initiation and spontaneous resolution of adjuvant arthritis (AA). We investigated synovial T-cell recruitment and mRNA expression of IL-17 and other important disease related cytokines, IFN-g , IL-2, IL-4, TNF and TGF-b in inguinal lymph node (ILN) and synovial membrane (SM). Arthritis severity was assessed by a numerical rating score and rats were sacrificed every 3±4 days postadjuvant induction. Further assessment involved qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
47
0
3

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 34 publications
(39 reference statements)
6
47
0
3
Order By: Relevance
“…In this study, we describe that IFN-γ is associated with protection against adjuvant arthritis (AA), which is considered to be a Th1-mediated disease. Our results validate and further enlarge the scope and implications of observations reported earlier in the AA model [23,24].…”
Section: Introductionsupporting
confidence: 90%
“…In this study, we describe that IFN-γ is associated with protection against adjuvant arthritis (AA), which is considered to be a Th1-mediated disease. Our results validate and further enlarge the scope and implications of observations reported earlier in the AA model [23,24].…”
Section: Introductionsupporting
confidence: 90%
“…This finding supports the reported findings of in vitro studies showing that IFN␥ has a potent negative effect on RANKL-induced osteoclastogenesis by degrading the RANK adapter protein TNF receptor-associated factor 6 (31). Other explanations also include the finding that in adjuvant arthritis, inhibition of IFN␥ in later disease exacerbates the disease, and our previous work shows high levels of synovial IFN␥ expression in this phase (32). Similar results are found in the immune-mediated model of experimental allergic encephalomyelitis, and it has been hypothesized that this reflects T regulatory cell activity (33).…”
supporting
confidence: 70%
“…It is possible that the percentage of positive cells would differ between the groups in other time points. It is well established that the expression of pro-infl ammatory cytokines (TNF, IFN-γ, IL-2 and IL-17) increases in the inguinal lymph nodes in the early stages of AA [37]. The expression of these cytokines is transient, with the exception of IFN-γ, showing secondary growth later in the course of the disease (from day 17 onwards).…”
Section: Discussionmentioning
confidence: 99%
“…The expression of these cytokines is transient, with the exception of IFN-γ, showing secondary growth later in the course of the disease (from day 17 onwards). Also, it was suggested that the initial increase in IFN-γ occurs within pro-infl ammatory response and that the subsequent increase may refl ect the activation of regulatory T cells [37]. Thus, it is possible that even at the peak of the disease, a signifi cant change in the population of T cells might be taking place; it is only that within the limited time period available we might have missed the narrow window of opportunity to detect these subtle differences between the experimental groups.…”
Section: Discussionmentioning
confidence: 99%